Xcribe an OCR tool for Latex - Casupanan, Uriel Norbert S. (1999)
Back then, we drained our faculties to come up with solutions to several equations given to use by our math professors. But now, we found ourselves lucky because there are a variety of mathematical softwares available in the market. They can be ready for solving different kinds of mathematical equations ranging from algebra, trigonometry to calculus. However, one basic point that XCRIBE would like to address is the "friendliness" of these softwares to users. Typing equations on the computer is always a tedious task for users since a lot of mathematical symbols are not defined on the keyboard. Every time the users want to use certain symbols, he has to get those symbols somewhere and insert it, which takes a lot of time especially if the user is working on several equations. XCRIBE is suggesting a way out of this situation by providing an off-line input system for equations or expressions that the users wish to solve. As an input to our system, handwritten equations are to be scanned in bi-tone mode. The scanned image would then undergo the process of segmentation. XCRIBE uses the connected-component method in partitioning the equations into individual characters. The characters enclosed by a bounding box would then be "trimmed" TO BE OF 48-pixel length. Each scaled character would next undergo a process called feature extraction, where each character is represented as a series of 1's and/or 0's. The resulting binary image will be used as an input vector to an artificial neural network for character recognition. The recognized characters are checked for ambiguities. The characters are then converted into Latex format.